Analysis of the condition and development prospects of a depressed economy (by the example of the Syrian Arab Republic) - O. V. Berezhnaya; M. Ayoub (Вестник Северо-Кавказского федерального университета)
Introduction. Depressive economy is one of the objects of analysis within the framework of anti-crisis management. Research of this kind provides better understanding of the causes of crises, their nature and optimal directions to tackle the crisis at the macroeconomic level. The experience of states with economies of various types offers an extensive layer of analytical material necessary for the purposes of anti-crisis management of countries and regions.Goal. The aim of the work is to study the historical background and the current state of the depressed economy using the example of the Syrian Arab Republic (SAR). Materials and methods. The information base of the study was made up of secondary data. They are a set of analytical articles and monographs by Russian and foreign authors analyzing various aspects of the Syrian economy; statistical materials of the Central Bureau of Statistics of Syria on the official website of the agency in the form of annual statistical digests; international statistics of various agencies and international organizations. The methodological tools are represented by a set of statistical methods: analysis of time series, structural indicators, coefficient analysis, groupings, index method, etc. The authors differentiated the application of these methods depending on the initial information and, therefore, allowed them to obtain optimal results for the purposes of the study. The work notes the shortcomings of the information base for analysis associated with the peculiarities of the functioning of the SAR economy in the analyzed period. The study period was the first two decades of the 21st century. Special attention is paid to a comparative analysis of the state of the Syrian economy before the war and at present.Results and discussion. The conducted research allows making a number of conclusions about the depressed state of the economy of the Syrian Arab Republic. The dynamics of the gross domestic product (GDP) was analyzed in terms of constant prices, current prices, in various currencies, per capita. Data from various sources were compared. Particular emphasis was placed on the difference in the sectoral structure of GDP in different periods and taking into account inflation. In addition, the dynamics and structure of the population of the Republic were studied with account of martial law, and an assessment of the performance of individual industries was given. The aspects that shape the potential of the country to overcome the crisis were identified.Conclusion. Conclusions are made about the main problems characteristic of the depressed economy of Syria. Directions for further research are proposed. Problems related to the availability and adequacy of disclosure of information about the Syrian economy are emphasized.